Analisis Prioritas Pengembangan Sektor Industri Pengolahan di Kabupaten Mimika - Sari, Yunita; Bakar, Abu (STIE Jambatan Bulan, 2022)
This study aims to determine the sub-sector of the manufacturing industry that can be prioritized for development in Mimika Regency. In order to achieve these objectives, this research uses descriptive research methods. The data used in this study include GRDP data by business field based on 2010 constant prices in Mimika Regency and Papua Province during the 2016-2020 period which was collected through documentation techniques. To answer the formulation of this research problem, a combination of Klassen Typology and Location Quotient analysis is used. A sub-sector of the manufacturing industry in Mimika Regency is classified as a sub-sector that can be prioritized for its development as a driver of economic growth. The results of this study indicate that the sub-sector of the Textile and Apparel Industry, the sub-sector of the Chemical, Pharmaceutical and Traditional Medicine Industry, and the sub-sector of the Rubber Industry. Goods from Rubber and Plastics, sub-sector of Non-Metal Mining Goods Industry, Other Processing Industry sub-sector; Repair and installation of machinery and equipment services is a sub-sector of the manufacturing industry that can be prioritized for development in Mimika Regency